A novel moniliformin derivative as pan-inhibitor of histone deacetylases triggering apoptosis of leukemia cells - Lu, Xiaohua; Yan, Ge; Dawood, Mona; Klauck, Sabine; Sugimoto, Yoshikazu; Klinger, Anette; Fleischer, Edmond; Shan, Letian; Efferth, Thomas (Biochemical pharmacology, 2021)
New and potent agents that evade multidrug resistance (MDR) and inhibit epigenetic modifications are of great interest in cancer drug development. Here, we describe that a moniliformin derivative (IUPAC name: 3‐(naphthalen‐2‐ylsulfanyl)‐4‐{[(2Z)‐1,3,3‐trimethyl‐2,3‐dihydro‐1H‐indol‐2‐ylidene]methyl}cyclobut‐3‐ene‐1,2‐dione; code: MCC1381) bypasses P-gp-mediated MDR. Using transcriptomics, we identified a large number of genes significantly regulated in response to MCC1381, which affected the cell cycle and disturbed cellular death and survival. The potential targets of MCC1381 might be histone deacetylases (HDACs) as predicted by SwissTargetPrediction. In silico studies confirmed that MCC1381 presented comparable affinity with HDAC1, 2, 3, 6, 8 and 11. Besides, the inhibition activity of HDACs was dose-dependently inhibited by MCC1381. Particularly, a strong binding affinity was observed between MCC1381 and HDAC6 by microscale thermophoresis analysis. MCC1381 decreased the expression of HDAC6, inversely correlated with the increase of acetylated HDAC6 substrates, acetylation p53 and α-tubulin. Furthermore, MCC1381 arrested the cell cycle at the G2/M phase, induced the generation of reactive oxygen species and collapse of the mitochondrial membrane potential. MCC1381 exhibited in vivo anti-cancer activity in xenografted zebrafish. Collectively, MCC1381 extended cytotoxicity towards P-gp-resistant leukemia cancer cells and may act as a pan-HDACs inhibitor, indicating that MCC1381 is a novel candidate for cancer therapy.
Gesehen am 04.10.2022